Amino- and Thiol- Polysilsesquioxane Simultaneously Coating on Poly(p-Phenylenetherephthal Amide) Fibers: Bifunctional Adsorbents for Hg(II) - Wang, Yunfeng; Qu, Rongjun; Mu, Yinglei; Sun, Changmei; Ji, Chunnuan; Zhang, Ying; An, Kai; Jia, Xinhua; Zhang, Yu (Frontiers in Chemistry, 2019)
A double reagents simultaneous functionalization (DRSF) was used to prepare porous polysilsesquioxane with NH2 and SH bifunctional groups (PAMPSQ) coated poly(p-phenylenetherephthal amide) (PPTA) fibers adsorbents (PPTA-AM) via in situ condensations with aminopropyltriethoxysilane (APTES) and mercaptopropyltriethoxysilane (MPTES). The PAMPSQ coated on the PPTA surface was in the form of nanoparticles and its morphology varied with the proportion of the reactants. The PAMPSQ exhibited loose open meso- or macroporous features. The functional groups utilization of PAMPSQ was much higher than those of polysilsesquioxane on the mono-functional adsorbents with thiol or amino groups. The selective adsorption of PPTA-AM adsorbents for Hg(II) in binary component metal ion systems indicated their potential application in environmental remediation. The adsorption mechanism of Hg(II) onto PPTA-AM was proposed.